Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4300/jgme-d-09-00054.1
|View full text |Cite
|
Sign up to set email alerts
|

Burnout During Residency Training: A Literature Review

Abstract: Educators need to develop an active awareness of burnout and ought to consider incorporating relevant instruction and interventions during the process of training resident physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
421
6
28

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(498 citation statements)
references
References 59 publications
(66 reference statements)
9
421
6
28
Order By: Relevance
“…13 Brazilian studies, on the other hand, reveal a prevalence between 20 and 50%, using the same instrument adopted by us in this study: the MBI questionnaire. Half of the residents of internal medicine at a philanthropic hospital in São Paulo met the criteria for burnout in 2012.…”
Section: Discussionmentioning
confidence: 72%
“…13 Brazilian studies, on the other hand, reveal a prevalence between 20 and 50%, using the same instrument adopted by us in this study: the MBI questionnaire. Half of the residents of internal medicine at a philanthropic hospital in São Paulo met the criteria for burnout in 2012.…”
Section: Discussionmentioning
confidence: 72%
“…Higher stress levels are more likely to be encountered during the head and neck oncology and junior years of residency. Identifying contributing factors, including lack of control, work planning/organization,3 lack of sleep, stress, and depression during training can potentially minimize further mental distress and medical error 1. By identifying otolaryngology residents at risk, program directors and the residents themselves may intervene earlier when patient care or resident well‐being is at risk.…”
Section: Resultsmentioning
confidence: 99%
“…There have been arguments for and against these changes, some believing that the number of procedures or experiences would increase and some arguing that they would decrease 31. Instituting mentoring programs, dedicated research, and/or dedicated teaching times have been found to improve resident satisfaction 3, 32. The Cedars‐Sinai Psychiatry Program has implemented a program via a wellness consultant to introduce cognitive‐, behavioral‐, and mindfulness‐based relaxation 3, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have attempted to determine the potential risk factors for burnout among residents. Excessive work hours [6,17,18] certain personality types [19,20] and depression [18,21,22] are among the correlates linked to higher rates of burnout. However, findings in the literature are inconsistent [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…According to Maslach and Jackson burnout is a syndrome characterized by emotional exhaustion (EE), depersonalization (DP), and reduced sense of personal accomplishment (PA) [5]. Burnout in resident physicians ranges between 30% and 70%, depending on the specialty and the criteria used to define the condition [6,7]. Burned-out residents may feel emotionally depleted and unable to give of themselves such that they develop a cynical attitude, dehumanize their patients, and devalue their own clinical performance [8].…”
Section: Introductionmentioning
confidence: 99%